Reciprocal Partnership Model as an Innovative Strategy in Strengthening the Financial Independence of State Madrasah - Apud Apud; Nana Suryapermana; As'ari; Asyniha Maulidya; Rizal (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
High dependence on DIPA and BOS funds has caused Madrasah Aliyah Negeri (MAN) 2 in Serang Regency to experience significant financial disruption since 2020. This dependence reflects the poverty crisis in education financing and the demand for new strategies to achieve financial independence for Islamic educational institutions. This study aims to technically examine how state madrasas can build an integrated and effective entrepreneurship system by optimizing internal resources and external partnerships based on a reciprocal model (reciprocal partnerships). Using a qualitative approach with a naturalistic paradigm, data was collected through in-depth interviews, non-participatory observation, and documentation with the madrasah principal, administrative staff, teachers, and external partners. Analysis was conducted using interactive methods that included data reduction, data presentation, and iterative conclusion drawing. The results show that the madrasah successfully achieved 80% of its self-financing target by utilizing cooperatives, a canteen, the Zakat Management Unit (UPZ), foster child programs, and collaboration with institutions such as the Banten Provincial Library and Archives Office. The implemented reciprocal partnership model has proven effective in expanding networks, strengthening literacy, and supporting educational programs without relying solely on the state budget. The main novelty of this research lies in the reciprocal partnership model within the context of religious-based state madrasahs, which has not been widely explored in the Islamic education management literature. The implications of this research emphasize the importance of visionary and entrepreneurial-oriented madrasah leadership in building an autonomous, adaptive, and financially sustainable institutional culture.